The Influence Of Liquidity, Productive Asset Quality And Operational Efficiency On Company Stock Prices : Study of Banks Going Public for the 2016-2020 Period - Wulansari, Tutut; Suwardi Suwardi; Firdaus, Firdaus; Purwanto, Dedik; Hibatullah, Ziyad; Choirul Marganis, Vedro (International Journal of Economics and Management Sciences, 2024)
The purpose of this study was to determine the effect of Liquidity, Earning Asset Quality, and Operational Efficiency on the stock price of banking companies. The stock price in the capital market will determine the value of a company, where the performance and health of the company affect its share price, as well as the views of investors.This research is descriptive quantitative research. The population in this study are publicly listed banking companies in Indonesia which are listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sample used in this study were 20 companies using the purposive sampling method. The data analysis technique used is multiple linear regression, classical assumption test, t test, F test, and the coefficient of determination R Square.The results of the partial test or t test show that Liquidity (LDR) has no significant effect on stock prices, Earning Asset Quality (NPL) has a positive and significant effect on stock prices and Operational Efficiency has a negative and significant effect on stock prices. While the simultaneous test or F test shows that together Liquidity (LDR), Earning Asset Quality (NPL) and Operational Efficiency (BOPO) have a simultaneous effect on stock prices.